Detection and measurement of the agonistic activities of PCBs and mono-hydroxylated PCBs to the constitutive androstane receptor using a recombinant yeast assay. Issue 7 (October 2015) - Kamata, Ryo; Shiraishi, Fujio; Kageyama, Shiho; Nakajima, Daisuke
Highlights PCBs and OH-PCBs were tested for their ability to activate the CAR. Most of the tested PCBs and OH-PCBs activated CAR-mediated transcription. The CAR activities of the PCBs were greatly changed by presence of a hydroxyl group. Several OH-PCBs were much more potent than their non-hydroxylated analogs.